Karakteristik Penderita Sindroma Terowongan Karpal (STK) di Poliklinik Instalasi Rehabilitasi Medik RS Dr. Kariadi Semarang 2006 - Lusan Maria T Tamba; Handojo Pudjowidyanto (MEDIA MEDIKA INDONESIANA, 2008)
ABSTRACTThe characteristics of carpal tunnel syndrome of patients in the medical rehabilitation (PMR) outpatient clinic Dr. Kariadi Hospital Semarang 2006Background: Carpal tunnel syndrome (CTS) is a common clinical disorder in daily practice, especially in the PMR outpatient clinic Dr. Kariadi Hospital Semarang. However it seems there is no pattern of patient characteristic and medical rehabilitation programs applied for the CTS patients. The objective of this study was to explore patient characteristics and the medical rehabilitation programs.Methods: The study was an observational descriptive study. Data were collected from medical records of new patients diagnosed with CTS in PMR Department Dr. Kariadi Hospital Semarang in 2006.Results: There were 34 patients (4% of 838 new patients) diagnosed with CTS, 32 (94,1%) were female and 2 (5,9%) were male, 18 (53%) with unilateral CTS and 16 (47%) with bilateral CTS. Most of them were 41-50 (38,2%) and 51-60 years old (35,3%) and dominantly were house wife (61,8%). The most frequent clinical manifestations were numbness (97%), with positive Tinel’s sign (88,2%). Electrodiagnostic examination was done in 17 subjects (50%). The most frequent medical rehabilitation program isultrasound therapy (76,5%), six times a week.Conclusion: CTS patients are predominantly women with positive Tinel sign, and therapy given is mostly ultrasound and ortotic prosthetic with splint.Key Words: carpal tunnel syndrome, clinical manifestation, medical rehabilitation programABSTRAKLatar belakang: Sindroma Terowongan Karpal (STK) merupakan gangguan yang sering ditemukan dalam praktek sehari-hari, khususnya di Poliklinik Instalasi Rehabilitasi Medik (IRM) RS Dr. Kariadi Semarang. Namun hingga saat ini belum diketahui karakteristik penderita dan program rehabilitasi yang diberikan. Penelitian ini bertujuan untuk mengetahui pola penderita STK dan program rehabilitasi medik yang diberikan.Metode: Penelitian bersifat observasional deskriptif. Data diperoleh dari rekam medis pasien dengan diagnosis STK yang berobat pertama kali ke Poliklinik IRM RS Dr. Kariadi Semarang tahun 2006, meliputi karakteristik penderita dan program rehabilitasi medik.Hasil: Selama 1 tahun (2006) didapatkan 34 penderita STK baru, yaitu 4% dari seluruh pasien baru (838 orang). Sebanyak 32 orang (94,1%) adalah perempuan dan 2 orang (5,9%) laki-laki, 18 (53%) unilateral dan 16 (47%) bilateral. Kelompok usia terbanyak adalah 41-50 tahun (38,2%) dan 51-60 tahun (35,3%). Pekerjaan terbanyak adalah ibu rumah tangga (61,8%). Keluhan/gejala terbanyak adalah parestesi (97%) dengan Tanda Tinel positif didapatkan pada 88,2% penderita. Pemeriksaan elektrodiagnostikdilakukan pada 17 orang (50%). Program rehabilitasi terbanyak diberikan adalah terapi ultrasound pada 26 orang (76,5%) dengan frekuensi setiap hari selama satu minggu.Simpulan: Penderita STK predominan perempuan dengan Tanda Tinel positif dan terapi yang diberikan adalah ultrasound dan splint ortotik prostetik.